Economic of Major Farming Systems in North Coastal Zone of Andhra Pradesh - K.N. Ravi Kumar,; B. Bapuji Rao,; K. Sree Lakshmi, (Journal of Agricultural Extension Management, 2025)
North Coastal Zone (NCZ) is characterized by rainfed agriculture and fertile soils suitable for raising a wide variety of crops round the year. Majority of the area in this zone is largely rainfed with meager irrigation sources. Nearly 80% of the farmers in this zone was adversely affected by drought conditions in the past 3-4 years, thereby, resulting in low crop productivity. Moreover, the adoption of scientific technologies in the crop production is on a low scale because of large scale illiteracy, lack of awareness on the mode of adoption of modern technologies and primitive outlook of the farming community. Hence, the farmer's income is low and unstable than the maximum they can realize from the existing potentiality of the zone. Further, the diversification of agricultural activities is very low in this zone, which otherwise reduces the risk and help in stabilizing the farm income besides providing a source of employment throughout the year. Only 20% of the farming community in this zone are taking up allied activities of agriculture like poultry, sheep rearing and sericulture. Since agriculture among the farmers is mostly on rainfed condition, it is a highly risky proposition and it can be sustained by mixed farming - a type of farming that combines crop production with one/more enterprises of allied activities of agriculture. This mixed farming facilitates the farmers for better utilization of farm by-products, stabilizing the annual net income, effective utilization of family labour for longer periods in a year and reduces the risk in agribusiness, thereby paves the way for sustainable agricultural production